Comparisons of commercial organic and chemical fertilizer solutions on growth and composition of lettuce. (28th May 2019) - Zandvakili, Omid R.; Barker, Allen V.; Hashemi, Masoud; Etemadi, Fatemeh; Autio, Wesley R.
Abstract: The objective of this experiment was to assess the effects of organic or chemical nutrient solutions on the growth and composition of lettuce ( Lactuca sativa L.) in greenhouse production. Hoagland and Arnon nutrient solution, an organic hydroponics solution, and no fertilization were factored with lettuce cultivars of different phenotypes, iceberg, romaine, loose head, and loose leaf. Lettuce growth was higher with Hoagland and Arnon solution than with the organic fertilizer or with no fertilization. The organic fertilizer increased growth above no fertilizer applied. Hoagland and Arnon solution gave the highest concentration of nitrogen, potassium, magnesium, and iron in the lettuce whereas lettuce grown with the organic fertilizer had the highest phosphorus. Plant nutrient accumulation differed slightly among the cultivars. Hoagland and Arnon solution produced high nitrate in leaves. Nitrate concentrations with organic or no fertilization were low. Loose head or loose leaf cultivars had higher nitrate than romaine or iceberg.